Construção e validação de checklist para a segurança do paciente no ato transfusional - Rambo, Christiani Andrea Marquesini (2021)
Introduction: the transfusion process encompasses various steps performed by several professionals. Blood transfusion is one of the most used therapies worldwide and involves complex procedures with risk for incidents and complications. Given the above, checklists are strategies that can improve the safety and quality of care, such as the surgical safety checklist. Regarding the transfusion process, it was found the lack of tools to check all of its steps. Objective: to design and validate a checklist for patient safety during the transfusion process. Method: this is a methodological study conducted in four steps. The first was composed of an integrative literature review, complemented with the recommendations of the current legislation, in order to collect the preliminary items of the checklist. These items were submitted to content validation by an expert committee, composed of health professionals working in transfusion procedures in the studied institution. After analysis of the results and adjustments, the first version of the checklist was produced. This tool was sent for content validation to an expert committee, composed of health professionals with high level of expertise in the field of hemotherapy, working in health institutions in various Brazilian states. After this step, the second version of the checklist was designed, which was submitted to a pre-test to analyze the clarity and understanding of the items with the target population. This audience included health professionals who will use the checklist during transfusion procedures at the researched institution. The validity of the tool was measured in all steps by means of the Content Validity Index (CVI) for each item and for the entire construct. A minimum agreement of 0.80 was established. The study was approved by the Research Ethics Committee of the Federal University of Santa Maria under opinion nº 3.800.128. Results: the preliminary checklist of items, obtained from the integrative review, consisted of 48 items and 80 sub-items. In the first validation step (expert committee), all items were considered valid, with CVI>0.80; however, change proposals were accepted, resulting in 31 items and 92 sub-items. These elements were submitted to the second validation step (expert committee), where 7 items/sub-items obtained CVI<0.80. After reformulations, exclusions, and suggested additions, the second version of the checklist was composed of 29 items and 90 sub-items. In the third validation step (pre-test), only one item did not reach the minimum established CVI, which was changed and submitted to a new round of evaluation by the same professionals, obtaining 100% agreement. The ultimate version of the checklist reached an overall CVI of 0.98 and was composed of 29 items and 90 sub-items, divided into 3 domains (Pre-transfusion, Transfusion, and Post-transfusion), which, in turn, were subdivided into 5 Blocks (Prescription, Compatibilization, Bedside identification, Installation, and Monitoring). Conclusion: the checklist showed content validity to be used as a strategy capable of providing greater safety to professionals and patients, as well as improvement in the quality of care provided to patients undergoing blood component transfusion.